(untitled) (Al-Qamar, 2024)
This article presents a research study on personality development in light of Quranic teachings. It explores various dimensions of human personality through interpretations of Quranic verses. The study delves into human creation, purpose of life, beliefs, acts of worship, and their effects on character building. It highlights the comprehensive principles of Islam as the foundation for character refinement and personal growth, guiding individuals towards success in both this world and the hereafter.